Efficacy of Commercially Available Quaternary Ammonium Compounds for Controlling New Zealand Mudsnails Potamopyrgus antipodarum. (3rd March 2016) - Stout, J. Benjamin; Avila, Brian W.; Fetherman, Eric R.
Abstract: The New Zealand mudsnail Potamopyrgus antipodarum is an invasive species that can be transported to and established in new bodies of water on gear used by aquatic professionals, anglers, and aquatic recreationists. Sparquat 256, a standard disinfectant for controlling the spread of mudsnails, was recently discontinued by the manufacturer. Our objective was to find an industrial-strength, commercially available quaternary ammonium compound (QAC) that could replace Sparquat 256 for disinfection purposes. The efficacy of three products—Quat 4, Green Solutions High Dilutions Disinfectant 256 (GS 256), and Super HDQ Neutral (Super HDQ)—were tested using bath disinfection at multiple concentrations and exposure durations. For bath disinfection purposes, GS 256 and Super HDQ were the most effective. Super HDQ caused higher mortality rates at 48 h postexposure and was therefore tested and found to be highly effective for spray disinfection to prevent transporting mudsnails on field equipment. Regardless of the QAC chosen, we recommend a bath disinfection rate of 0.4% and a spray disinfection rate of 0.8% QACs in solution with an exposure duration of 10 min. These concentrations meet or exceed minimum effective disinfection requirements for quagga mussels Dreissena rostriformis bugensis, zebra mussels Dreissena polymorpha, whirling disease Myxobolus cerebralis, and chytrid fungus Batrachochytrium dendrobatidis . Received January 8, 2015; accepted November 8, 2015.